The relationship between the macroeconomic indicators and performance of stock market in Malaysia / Muhammad Faiz Mohd Arif - Mohd Arif, Muhammad Faiz (Faculty of Business and Management, 2015)
The study aims at examining how macroeconomic indicators affect the performance of stock market in Malaysia. The paper employs the latest estimation macroeconomics indicators that affect the performance of stock market in Malaysia. Stock market seems to be volatile and the reasons for the rise and fall of the stock return can be very complicated. Stock market performance and economic condition of a country is interrelated and has been an important debating issue. Thus, the macroeconomics factors can affect stock market performance in Malaysia. The sample data were derived from four variables such as exchange rate, gross domestic product, interest rate and foreign direct investment. The dependent variable is stock market performance and was indicated by using KLCI. The methods that will be used were multiple regressions and e-views. Thus, the independent variables are the exchange rate, gross domestic product (GDP), interest rate and foreign direct investment. It can be used in order to identify the performance of stock market in Malaysia. Based on the theories, the result showed that there are positive and negative relationships towards the stock market performance